CLOUD COMPUTING: A NEW ERA - S, Namasudra (جامعة الوادي university of eloued, 2018)
Cloud computing is a new paradigm of Information Technology (IT), which allows users to access software, hardware and data from the cloud server. Cloud computing provides many services to the users. Nowadays, access control and security are two most critical problems with cloud computing. Access control can be defined as a procedure by which users can access data from the cloud server. At the time of accessing data, there are many problems, such as data security, high data accessing time, data loss, overhead, data redundancy, etc. Several access control models have been already developed based on attribute-based encryption. In the first part of this paper, a brief discussion of fundamentals of cloud computing are presented. Moreover, allthe issues of cloud computing are also discussed in this paper. Finally, future work directions have been identified for the cloud computing environment.
aretical
Keywords: Cloud Computing, Cloud Service Provider, Data Owner, Access Control, Encryption.